O exercício profissional de assistentes sociais no acolhimento institucional para crianças e adolescentes nos municípios de Cuiabá e Várzea Grande - Silva, Iris Rodrigues da (2021)
The dissertation deals with the professional practice of Social Workers in the Institutional Shelter Service for Children and Adolescents having as locus the municipalities of Cuiabá and Várzea Grande. Considering that the State of Mato Grosso has a total of ninety Institutional Shelters for children and adolescents, we chose to conduct the research in the cities of Cuiabá and Várzea Grande, as these two cities have a higher concentration of these institutions, besides being the two largest cities in the State. The municipality of Cuiabá has eight shelters and six social service professionals, and the municipality of Várzea Grande has a total of six shelters and a total of three social service professionals in the Technical Reference Team. To analyze the professional practice of Social Workers inserted in the Reception Service, a qualitative approach was used, with exploratory research, thus providing the approximation of something little known or explored, since there is still little research referring to the professional performance of social workers in institutional reception services. In this sense, a survey of bibliographic and documental data was also carried out, as well as interviews with the professionals from the sheltering service, using semi-structured interviews, providing a closer approximation with the interviewees. Translated with www.DeepL.com/Translator (free version) From the analysis of the collected data, it was possible to perceive difficulties in the process of articulation among the dimensions that should constitute the professional exercise, on the part of some of the professionals. This is a concern, because this lack of articulation among the dimensions can lead to thoughtless, short-termist practices that do not change reality, but rather maintain it. Another important point was the fragility identified regarding the realization of the practice systematization, according to the Social Workers, hampered by the dynamics of the demands that reach the services, and which does not allow them to organize and plan the actions. In addition to these points, attention should be paid to the situation of institutions, the fragility in the networks of guarantees of rights, and of the social assistance network, in which there is a lack of services, promotion and prevention to avoid reception as well as for follow-up after the reinsertion. In view of the above, it is necessary to create spaces for discussion of professional practice with these professionals that can enable the challenges analysis of carrying out a professional practice in accordance with the profession EthicalPolitical Project, a critical, reflective practice in accordance with the socio-historical reality and with the broader project that encompasses the working class, as well as training processes that contribute in this direction.